Athletic performance - Grubb, H.
Which is the best world record? Or, for recreational athletes, which is your best race performance, given that they are at different distances? Athletics world records can be used to compare athletic performances, at all levels. We fit a model to these which describes change in performance with distance of the race. The basic assumption is that the best times in the world close to the world records are equally good. By looking at the residuals from this model, we can find which records appear to be better. The model can then be used to compare races at any distance, whether these were at 100% of the average world record performance, or anywhere below this. A brief summary of these ideas is given below. Links/tools Performance calculator - JavaScript application - input distance and time and get a calculation of your performance as a % of the world records and age-group WRs (updated September 15 1999). Race Pace calculator - JavaScript application gives mile or km splits for any distance Excel spreadsheet and VBA functions only with performance calculations (including age-group world records). Age-grading - compares age-group world records and WAVA factors. WAVA calculator - Javascript application to lookup WAVA factors for track and field events - can be downloaded for off-line use. Swimming records show a similar pattern and a simple model gives us the average benefit gained from turning at each end of the pool Data - includes original record data, spreadsheets with calculations/models, tables of equivalent performances and links to athletics sites. For more details of the models see the paper: Models for comparing athletic performances. (PostScript) (The Statistician, 1998, 47, 509-521). Presentation at RSS98, Glasgow, September 1998 (pictures below) Presentation at British Association, Festival of Science, Sheffield, 17th September 1999 (slides as PostScript and PDF - 5x4xA4). Calculating Championship Performances - article in The Fellrunner magazine, February 1999.